2014
DOI: 10.1007/s00535-013-0928-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human T-lymphotropic virus type 1 coinfection on the development of hepatocellular carcinoma in patients with hepatitis C virus infection

Abstract: HTLV-1 coinfection may contribute to the development of HCC in patients with chronic HCV infection, especially in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…23 The present study data, however, do not support this hypothesis, since there was no difference in HTLV-1 PVL or HCV viremia among the groups. Tokunaga et al 43 also described an increased risk of HCC during HCV/HTLV-1 co-infection, but only in female patients. Of note, most of the HCV/HTLV-1 co-infected individuals in the present study group were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The present study data, however, do not support this hypothesis, since there was no difference in HTLV-1 PVL or HCV viremia among the groups. Tokunaga et al 43 also described an increased risk of HCC during HCV/HTLV-1 co-infection, but only in female patients. Of note, most of the HCV/HTLV-1 co-infected individuals in the present study group were male.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of HCV/HTLV-1 co-infection in liver disease in patients with chronic hepatitis C has been evaluated in prospective and retrospective studies in Japan. 23,43 These studies reported that HTLV-1 was found to worsen the clinical course of HCV infection, contributing to the development of HCC in these patients. The authors suggest that an impaired T-cell response resulting from HTLV-1 infection may interfere with HCV clearance during coinfection, leading to chronic liver damage and an increased risk of hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other Japanese studies of HCV/HTLV-1 co-infection in PWID showed associations with liver disease (6-fold increased risk) [18] and liver cancer mortality (2.6-fold increased risk) [19] , leading to the hypothesis of an HTLV-1-induced immune modulation and inflammatory cytokine dysregulation that could affect HCV persistence and progression to liver disease [20,21] . In contrast to the Japanese findings, however, two Brazilian studies [22,23] of HCV/HTLV-1 co-infection provide epidemiological and immunological evidence of a higher rate of spontaneous clearance of HCV in patients with HIV/HTLV-1 co-infection as compared to patients harbouring only an HIV/HCV co-infection or an HCV mono-infection.…”
Section: Clinical Implications Of Hcv/htlv-1/2 Co-infectionmentioning
confidence: 99%
“…Only one study performed in an endemic area, Japan, showed a high prevalence of HTLV-1 among HCV-infected individuals (21.1% and 10.5% with or without hepatocellular carcinoma, respectively) [3].…”
Section: Dear Editormentioning
confidence: 99%